Electronic quenching of OH A 2Σ+ induced by collisions with Kr atoms. - Lehman, J; Lester, M; Kłos, J; Alexander, M; Dagdigian, P; Herráez-Aguilar, D; Aoiz, F; Brouard, M; Chadwick, H; Perkins, T; Seamons, SA (American Chemical Society, 2013)
Electronic quenching of OH A (2)Σ(+) by Kr was investigated through experimental studies of the collision cross sections and the OH X (2)Π product state distribution. The quenching cross sections decrease with increasing rotational excitation in the excited OH A (2)Σ(+) electronic state. The OH X (2)Π products of quenching exhibit a significant degree of rotational excitation but minimal vibrational excitation. Complementary theoretical studies of the OH (A (2)Σ(+), X (2)Π) + Kr potential energy surfaces (PESs), nonadiabatic coupling, and quasiclassical trajectory calculations were carried out to elucidate the quenching dynamics. Accurate PESs for the two lowest diabatic states of A' symmetry were computed along with the angularly dependent coupling between them. Coupling in nearly linear HO-Kr configurations provides the mechanism for the observed electronic quenching. A deep attractive well on the OH A (2)Σ(+) + Kr PES facilitates access to this region of strong coupling. Surface-hopping quasiclassical trajectory calculations yielded quenching cross sections and a OH X (2)Π product rotational distribution in good accord with experimental observations.